Связь права и литературы как новое направление юриспруденции - Хижняк, Ю. В.; Khyzhniak, Y. V. (Одеса : Юрид. л-ра, 2012)
In the article contained comparative analysis of understanding of humanities in Europe and America on the example of acquisition of scientific status American Criticism of Oratory.
Хижняк Ю. В. Связь права и литературы как новое направление юриспруденции / Ю. В. Хижняк // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 171-178.
Keywords: оратороведение; правоведение; системный подход; нормативно-гуманитарная наука; ораторознавство; правознавство; системний підхід; нормативно-гуманітарна наука; Criticism of Oratory; jurisprudence; systems approach; normative-humanitarian science